The effect of noise on health and quality of life - Piotrowski, Jan; Zatoński, Mateusz; Puła, Michał; Szydełko-Paśko, Urszula; Zub, Krzysztof (Family Medicine & Primary Care Review, 2025)
Exposure to noise is unavoidable in everyday life. It can cause adverse health effects, both auditory and non-auditory, such as hypertension, elevated levels of catecholamines, cardiovascular disease, cognitive impairment, irritability, and sleep disturbance. One of the most common effects of chronic noise exposure is noise-induced hearing loss. Given the increasing rate of urbanization and industrialization, noise should be considered a serious health risk. Many studies have shown how noise affects human beings and the implications of chronic noise exposure. This systematic review presents the results of selected studies on the public health impact of chronic noise exposure. The aim of this work was to raise public awareness of the problem of the effects of noise on health and quality of life, specifically the necessity of undertaking a noise prevention program. Noise-induced hearing loss has been shown to be gender-dependent, with men being more exposed than women, despite equivalent noise exposure and the same age. The harmful effects of noise have been shown to increase susceptibility to mental illnesses such as depression and anxiety. Children are particularly vulnerable to noise, which affects their attention and learning. Prevention programs, including raising awareness among parents and children about the potential risks of noise exposure, need to be undertaken. Pediatricians can have an impact on reducing children’s exposure to noise through screening children’s hearing and educating parents about the health effects of noise.